Oracle Fusion developer guide [ building rich Internet applications with Oracle ADF business components and Oracle ADF Faces - Nimphius, Frank; Munsinger, Lynn , 1976- (McGraw-Hill, 2010)
"Oracle Fusion Developer Guide goes beyond the predominantdrag-and-drop methods in Oracle JDeveloper 11g and provides a wealth of examples that address common development scenarios when using Oracle Fusion Middleware.Work with Oracle JDeveloper 11g, define navigation rules, accept and validate user input, build page layouts and skins, and incorporate drag-and-drop functionality into web applications. This authoritative resource also explains how to secure and internationalize your applications"--Resource description page